The Acquisition of 21st-Century Skills Through Video Games: Minecraft Design Process Models and Their Web of Class Roles. (June 2020) - Hewett, Katherine J. E.; Zeng, Guang; Pletcher, Bethanie C.
Background. Qian and Clark reported that little is known on the acquisition of21st-century skills throughvideo games and noeducational model exists on how to best teach these skills in the classroom. Studies that exploreeducational model s exhibited throughvideo games like Minecraft contribute to the growing body of research in the field of game studies, game-based learning, and virtual environments. Aim. The purpose of this qualitative case study was to explore the21st-century design processes, skills, and behaviors of high schoolgamers in order to generate aneducational model that illustrates how those classroomgamers attempted to critically think, create, communicate, and collaborate (Four Cs) in Minecraft . Method. The triangulated data collection included six qualitative case study interviews, observation data (with demographics) from thirteen participants, and visual artifacts from six classes grounded in social constructivist, social constructionist, and interpretivist theories. It should be noted that ninety-five students collaborated with the participants on the six Minecraft projects. Results. The data collection generated twoeducational Four Csmodel s that illustrate the participants' leadership and design processes. Four21 st -century themes emerged from the research study: 1.) Leadership : Models for Design 2.) Navigating the 3D World, 3.) Think Outside-the-Box, and 4.) Real-world Connections . Conclusions. It can be concluded that Minecraft can help students learn to problem-solve, improve their research skills, be resourceful, multitask, and develop their social skills through teamwork (Four Cs). When students are given a task in Minecraft they will self-organize and student leaders will emerge. Minecraft challenged the participants to assess a problem, analyze it from another perspective, and find a creative solution collaboratively.